Complete Adipose Replacement of Bilateral Medial Gastrocnemius Muscle - A Cadaveric Case Report - Nichols, Charles; Liu, Elizabeth; Liu, Howe (Academia Anatomica International, 2020)
Sarcopenia and infiltration of intermuscular adipose tissue are often seen in older adults due to aging process, but a muscle is completely replaced by adipose tissue is rarely reported. In this cadaveric case, we describe an observation of bilateral symmetric adipose replacement of the medial gastrocnemius muscles (GM) on both left and right leg in an 82-year old Caucasian female, whose cause of death was advanced dementia. The white adipose tissue replaced the entire medial GM muscle belly with pennate-like arrangement, indicating adipose tissue infiltration very likely into the original muscle cells. Where and how these adipose tissues come from are discussed.